Description of Pain Levels in Elderly Patients with Immobilization at Ruang Anggrek RSU Negara - T. Ni Made Dewi Erawati; Sang Ayu Ketut Candrawati; Ni Luh Putu Dewi Puspawati (PROFESSIONAL HEALTH JOURNAL, 2024)
Introduction. Impaired mobility in the elderly is a condition of limited movement in the function of one or more of the body's extremities which can affect the independence of the elderly in carrying out daily activities physically and psychologically. Objectives. To determine the description of pain level in elderly patients with immobilization history. Methods. Descriptive research with a retrospective approach, examining the medical records of elderly patients with immobilization history who were treated at Ruang Anggrek RSU Negara during 2022-2023. Data analysis to calculate the percentage of each pain level in elderly patients with immobilization. The tool used to measure pain was the numerical rating scale (NRS). Results. The number of elderly patients with immobilization history treated at Ruang Anggrek RSU Negara during 2022-2023 was 105 patients, most of whom were female (51.4%) and in the age group 60-69 years old (47.6%). The most frequent comorbidity was hypertension (20.0%) with myalgia (86.7%). Based on pain level, it was found that 67.6% had mild pain, 29.5% moderate pain, and 2.9% severe pain. Mild pain was more often accompanied by myalgia (91.55%). Severe pain was more often accompanied by arthralgia (66.67%) and with ≥2 comorbidities (66.67%). Conclusions. The pain level in elderly patients with immobilization history was mostly mild, most of them were female with comorbid hypertension accompanied by myalgia. This mild pain was related to the most common cause which was muscle pain (myalgia). Joint pain (arthralgia) tends to cause more severe pain. Hypertension tends to worsen the course of pain